2019
DOI: 10.1371/journal.pone.0223861
|View full text |Cite
|
Sign up to set email alerts
|

Differential immunomodulation of T-cells by immunoglobulin replacement therapy in primary and secondary antibody deficiency

Abstract: Patients with primary or secondary antibody deficiency (PAD or SAD) are at increased risk of recurrent infections that can be alleviated by immunoglobulin replacement therapy (IRT). In addition to replenishing antibody levels, IRT has been suggested to modulate immune response in patients with antibody deficiency. Although both commonly treated with IRT, the underlying causes of PAD and SAD vary greatly, suggesting differential modulation of T-cell function that may lead to different responses to IRT. To explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Absolute numbers of B cells, NK-cells, CD4 and CD8 T cells did not differ between IgGsd patients and healthy controls and were not affected by IgRT, which is in line with a previous report of an unselected cohort of PAD [24]. Deeper analysis of B and T cells subsets in our study showed that activated (CD25 + ) B cells were lower in IgGsd and normalized during IgRT.…”
Section: Discussionsupporting
confidence: 92%
“…Absolute numbers of B cells, NK-cells, CD4 and CD8 T cells did not differ between IgGsd patients and healthy controls and were not affected by IgRT, which is in line with a previous report of an unselected cohort of PAD [24]. Deeper analysis of B and T cells subsets in our study showed that activated (CD25 + ) B cells were lower in IgGsd and normalized during IgRT.…”
Section: Discussionsupporting
confidence: 92%
“…1 As IVIG contains antibodies to diverse pathogens, the main goal of low-dose replacement therapy is to prevent recurrent infections in primary immunodeficient patients or in patients with recurrent infections with secondary immunoglobulin deficiencies. Several lines of evidence also suggest that low-dose IVIG therapy can exert positive effects on the cellular immune compartment, depending on underlying immunodeficiency [8][9][10][11][12] . In contrast, most autoimmune conditions require high dose therapy.…”
Section: Introductionmentioning
confidence: 99%
“…IVIG is also widely used to treat necrotizing soft tissue infections. It is also used for various autoimmune, inflammatory neurological, skin, and immunodeficiency diseases, as well as in the case of COVID-19 and reproductive medicine [14,15,16,17]. The meta-analysis of available clinical studies on the use of IVIG in Group A streptococcal toxic shock syndrome indicates benefits in terms of patient survival after severe septic shock [18].…”
Section: Introductionmentioning
confidence: 99%